Geographical distribution and risk factors for Echinococcus granulosus infection in peri-urban wild dog populations. (December 2019) - Harriott, Lana; Gentle, Matthew; Traub, Rebecca; Cobbold, Rowland; Soares Magalhães, Ricardo
Abstract: The transmission of zoonotic pathogens associated with wildlife in peri-urban environments can be influenced by the interplay of numerous socioecological factors. Echinococcus granulosus is known to be common within peri-urban wild dog populations however knowledge of the factors that influence its presence is limited. We investigated the demographic distribution of adult cestode abundance (ACA: defined as the product between prevalence of infection and adult cestode infection intensity) and the role of the physical environment, climate and individual factors in determining the geographical variation of E. granulosus infection in wild dog populations from southeast Queensland and surrounds. Our results align with previous studies that show significant E. granulosus aggregation in that 15.8% of peri-urban wild dogs sampled were responsible for ∼70% of the total adult cestode infection intensity. On average, female dogs were found to have a higher ACA than male dogs, and the average ACA generally decreased with age. Significant geographical variation was found in the prevalence of E. granulosus, with a strong propensity for clustering. The average size of clusters was 22.5 km. The probability of finding E. granulosus infection significantly increased with maximum temperature, relative humidity, and rainfall, and after accounting for individual and climatic variables, the model accounted for the majority of the spatial dependence in prevalence. Our predictive map of E. granulosus prevalence in peri-urban wild dogs confirms that E. granulosus is highly endemic in the eastern Australia study area. The prediction map provides a useful tool for targeting potential disease management strategies in peri-urban areas, where broad scale management of wild dog populations is difficult to implement. Graphical abstract: Image 1 Highlights: E. granulosus is common in peri-urban wild dog populations. E. granulosus worm burdens in peri-urban wild dogs are highly aggregated. Bitches and pups have higher adult cestode infection intensity than males and older animals. High endemic regions of E. granulosus are present within human developed environs.